Gastric antral duplication cyst: A case report - Kaniz Fathema; MD. Benzamin; Fahmida Begum; Fahmina khanam; Md Mahamudul Hasan; Mizu Ahmed; Md Wahiduzzaman Mazumder; Salahuddin Al Azad; Bishnu Pada Dey; A S M Bazlul Karim (Indonesian Pediatric Society, 2021)
Alimentary tract duplications may be symptomatic or may be discovered incidentally. They are named for the organ with which they are associated.1 Congenital gastrointestinal (GI) tract duplication cysts are commonly located in the ileum (53%), mediastinum (18%), colon (13%), stomach (7%), duodenum (6%), rectum (4%), or oesophagus (2%)2. A single theory is insufficient to explain all types of duplications.3 Children may present with symptoms like vomiting, abdominal pain, lumps, or weight loss.4 The presence of ectopic gastric mucosa and the potential for malignancy remain matters of concern.2 Surgical management is essential for these rare cysts.5 We encountered a Bangladeshi boy with a gastric duplication cyst (GDC) that was pre-operatively diagnosed as a pancreatic cyst. A variety of imaging modalities failed to indicate GDC before the operation. Here we present the clinical course of the case and discuss the difficulties and problems in diagnosing GDC.